2017
DOI: 10.1007/s40145-017-0229-1
|View full text |Cite
|
Sign up to set email alerts
|

Pressureless sintering of ZrC with variable stoichiometry

Abstract: This paper presents the experiments on the synthesis of zirconium carbide (ZrC) using carbothermal reduction of zirconia (ZrO 2 ). The ratio of ZrO 2 :C is used to adapt ZrC x O y with x < 1 or ZrC + C. The modification of ZrC x O y and the total carbon amount allows the use of pressureless sintering method in combination with sintering temperatures ≤ 2000 ℃. Fully densified ZrC products are obtained. The relevant details of ZrC formation are investigated by X-ray diffraction (XRD). The sintered products are c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…This result was also consistent with other studies whose TEM analysis revealed amorphous carbon on the ~100 nanometre scale 24 . The extended network of intra and intergranular depressions as seen in the SEM images has also been observed in previous studies 12,15,19,24 . These features were seen to be comprised of sp 2 pristine, 'partially destroyed' graphite and amorphous carbon structures can be seen from the Raman spectra of samples produced in this study.…”
Section: Discussionsupporting
confidence: 87%
“…This result was also consistent with other studies whose TEM analysis revealed amorphous carbon on the ~100 nanometre scale 24 . The extended network of intra and intergranular depressions as seen in the SEM images has also been observed in previous studies 12,15,19,24 . These features were seen to be comprised of sp 2 pristine, 'partially destroyed' graphite and amorphous carbon structures can be seen from the Raman spectra of samples produced in this study.…”
Section: Discussionsupporting
confidence: 87%
“…2 Similarly, variable carbon stoichiometry is exhibited by other TMCs, such as TiC x , [3][4][5] HfC x , 6,7 VC x , 8 NbC x , 3,9 TaC x , 10,11 and WC x . 12 Carbon stoichiometry affects the sinterability, [13][14][15] mechanical properties, 16,17 electrical properties, 18 and radiation resistance 19 of ZrC x ceramics. Short-and long-range ordering of carbon vacancies in nonstoichiometric carbides have both been studied theoretically.…”
Section: Introductionmentioning
confidence: 99%
“…Five measurements were taken for each sample and average of hardness and density results belonging to the composites are presented in Table I. Since ZrC has a theoretical density of 6.73 [7], the density of the composite increases with the addition of ZrC. However, there was a slight decrease in density with the increase of the reinforcement amount.…”
Section: Resultsmentioning
confidence: 99%